Krisis Identitas Siwa Di Era Digital: Tantangan Dan Peran Strategis Bimbingan Dan Konseling Sekolah - Muhibbuddin, Hadziq; Aisyah Fitri, Geby (Journal of Islamic Education Counseling, 2025)
This study examines the phenomenon of adolescent identity crisis in the digital era and the role of guidance and counseling services in addressing the issue. The study employed a qualitative approach using a literature review method by analyzing various scientific sources related to adolescent development, identity formation, digital media influence, and counseling interventions. The findings indicate that rapid technological development and social media exposure significantly affect adolescents’ self-concept and identity formation. In addition, lack of parental attention, unhealthy social environments, and limited emotional support contribute to the emergence of identity confusion among adolescents. The impacts include low self-esteem, social anxiety, difficulty determining life goals, and deviant behavior tendencies. Guidance and counseling teachers play an important role in helping adolescents develop positive identities through preventive and developmental services such as individual counseling, group psychoeducation, character education, and digital literacy programs. Therefore, collaborative support among schools, families, and communities is necessary to assist adolescents in facing developmental challenges in the digital era.